Mitochondrial heterogeneity in cells - Collins, Tony (Henry Stewart Talks, 2007)
Levels of mitochondrial heterogeneity, Subcellular heterogeneity, Membrane potential, Permeability transition, Calcium uptake, Morphology: network or discrete?, Live cell mitochondrial 3D reconstruction, Fluorescence Recovery After Photobleaching (FRAP), Electrical continuity, Atypical networks
Archived at 2018/05/31